Christian Morality for the Nordic Nation: A Circulating Knowledge in Times of Crisis - Boije, Erika (A journal of church and state, 2025)
This article discusses the role of Christianity in Nordic nation-building and the development of the democratic welfare state in the nineteenth and twentieth centuries. The theoretical concept of circulation of knowledge is used to analyze how ideas of Christianity and morality circulated within and between two Nordic countries, Finland and Sweden, in periods of perceived crisis and how they were incorporated into national narratives and images of ideal citizens. Three historical examples are examined: the Finnish author Zacharias Topelius’s public literary nation-building, the promulgation of a new curriculum for Swedish primary schools during the interwar period, and the efforts to safeguard Swedish political independence, culture, and national identity during the Second World War.